Challenges Facing EFL Students of English Department in Some Topics of Grammar - Jwan Ahmed Mustafa (Zanco Journal of Humanity Sciences)
To master a language, it is essential to study its grammar which is one of the most difficult aspects of that language. Grammar is regarded as the subject that provides a whole cohesive system concerning the formation and transmission of language. Teaching grammar has been ever since a source of controversy in the teaching of second and foreign languages. Students acquire the feeling of discomfort whenever they hear the term “grammar”, however, teachers try to do their best to make grammar interesting and non-threatening. English grammar has been regarded as a system of syntactic rules that determines the order and patterns in which words are patterned to form sentences. The appropriateness of an utterance requires a good knowledge of grammar. To master English, it is necessary to know various forms and usages which confuse English as second/foreign language for (ESL/EFL) learners. Learners may learn new grammar rules every day, but they find difficulties applying them when they speak or write in English. This research tries to focus on the grammar topics that college students find challenging. So, it aims at mainly determining easy and difficult grammar topics through learners′ perspective.  It also tries to provide some solutions for the students to overcome the difficulties they face, so this research has pedagogical significance since it provides some important recommendations and further suggestions for the purpose of teaching these grammatical subjects.